Bài 15.Rút gọn rồi tính giá trị các biểu thức sau
1) \(8x^3+12x^2+6x+1\) tại x=-2
2) \(8x^3-12x^2+6x-1\) tại x= \(-\frac{1}{2}\)
3) \(\left(1-2x\right)^2-\left(3x+1\right)^2\) tại x=-2
4) \(\left(2x-3y\right).\left(4x^2+6xy+9y^2\right)\) tại x \(-\frac{1}{2}\):y=\(-\frac{1}{3}\)
1) \(8x^3+12x^2+6x+1=\left(2x\right)^3+3.\left(2x\right)^2.1+3.2x.1^2+1^3\)
\(=\left(2x+1\right)^3=\left(2.-2+1\right)^3=-27\)
2) \(8x^3-12x+6x-1=\left(2x\right)^3-3.\left(2x\right)^2.1+3.2x.1^2-1^3\)
\(=\left(2x-1\right)^3=\left(2.-\frac{1}{2}-1\right)^3=-8\)
3)\(\left(1-2x\right)^2-\left(3x+1\right)^2=\left(1-2x+3x+1\right)\left(1-2x-3x-1\right)\)
\(=\left(x+2\right)\left(-5x\right)=\left(-2+2\right).\left(-5.-2\right)=0\)
4) \(\left(2x-3y\right)\left(4x^2+6xy+9y^2\right)=\left(2x-3y\right)\left[\left(2x\right)^2+2x.3y+\left(3y\right)^2\right]\)
\(=\left(2x\right)^3-\left(3y\right)^3=\left(2.-\frac{1}{2}\right)^3-\left(3.-\frac{1}{3}\right)^3=-1-\left(-1\right)=0\)
1) Ta có : \(8x^3+12x^2+6x+1\)
\(=\left(2x+1\right)^3=\left(2.-2+1\right)^3=\left(-3\right)^3=-27\)
b) \(8x^3-12x^2+6x-1\)
\(=\left(2x-1\right)^3=\left[2.\left(-\frac{1}{2}\right)-1\right]^3=-8\)